Review: Syarat Pangan yang Berpotensi sebagai Probiotik ditinjau dari Nutrisinya - Ilmiaty Rahmi; Novriyanti Lubis; Dang Soni (Program Studi Teknologi Pangan, 2020)
Yogurt and Kefir are foods that have potential as probiotics. The presence of live LAB (Lactic Acid Bacteria) indicates that this product has the potential as a probiotic food. The purpose of this review is to evaluate food products that have the potential as probiotics such as yogurt and kefir based on the SNI 2981: 2009 standard for yogurt and the CODEX STAN 243-2003 standard for kefir in terms of nutrition. The search method in this article review uses online literature through the Google Scholar site. The results of this review article are probiotic yogurt containing cow's milk and sheep's milk in the same proportion (1: 1); cow's milk yogurt with the addition of seaweed extract (Sargassum polycystum) with a concentration of 0,22 and 0,44%; cow's milk yogurt added with watercress extract (Nasturtium officinale, R. Br); and goat's milk kefir stored at temperatures (-1 to -5 oC, 1 to 5 oC, and 6 to 10 oC) and storage time (10, 20, and 30 days) is a food that has the potential to be a probiotic that has met SNI 2981: 2009 standards and the CODEX STAN 243-2003 standards in terms of nutrition.